2013
DOI: 10.1016/j.bbamem.2013.07.029
|View full text |Cite
|
Sign up to set email alerts
|

A structure–activity relationship study of flavonoids as inhibitors of E. coli by membrane interaction effect

Abstract: Flavonoids exhibit a broad range of biological activities including antibacterial activity. However, the mechanism of their antibacterial activity has not been fully investigated. The antibacterial activity and membrane interaction of 11 flavonoids (including 2 polymethoxyflavones and 4 isoflavonoids) against Escherichia coli were examined in this study. The antibacterial capacity was determined as flavonoids>polymethoxyflavones>isoflavonoids. Using fluorescence, it was observed that the 5 flavonoids rigidifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(152 citation statements)
references
References 35 publications
6
137
1
8
Order By: Relevance
“…This indicated that the type of substituent group at position 4′ in the B ring is crucial to the antibacterial effects of the two flavonoid compounds. There are four additional free hydroxyls in the glucoside of liquiritin which might be the key factor in inducing the antibacterial effect, indicating that the introduction of hydroxyl group at position 4′ in the B ring enhances the antibacterial effects of flavonoid compounds, which is in agreement with previous reports (Alcaráz et al 2000;Sato et al 1997;Tim Cushnie and Lamb 2005;Wu et al 2013). …”
Section: Structure-effect Relationshipsupporting
confidence: 90%
See 3 more Smart Citations
“…This indicated that the type of substituent group at position 4′ in the B ring is crucial to the antibacterial effects of the two flavonoid compounds. There are four additional free hydroxyls in the glucoside of liquiritin which might be the key factor in inducing the antibacterial effect, indicating that the introduction of hydroxyl group at position 4′ in the B ring enhances the antibacterial effects of flavonoid compounds, which is in agreement with previous reports (Alcaráz et al 2000;Sato et al 1997;Tim Cushnie and Lamb 2005;Wu et al 2013). …”
Section: Structure-effect Relationshipsupporting
confidence: 90%
“…Using this microcalorimetric method, some critical information including the real-time metabolic power-time curve together with quite a few quantitative thermokinetic parameters of E. coli growth in the presence of the test compounds was obtained. This was previously not possible by traditional microbiological methods including the agar cup method and the serial dilution method (Alcaráz et al 2000;Dastidar et al 2004;Liu et al 2000;Tim Cushnie and Lamb 2005;Wu et al 2013) but was very crucial in the antibacterial assessment (Ferreira et al 2015;Guo et al 2012;Kong et al 2012). Combined with chemometric approaches, such as SA, MANOVA, and PCA, the antibacterial effects of the two flavonoid compounds on E. coli were quickly and systematically evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of phenolic groups may attribute to their relative toxicity to microorganism because of increase in hydroxylation causing greater toxicity [37]. The difference in the antibacterial activity can be attributed to the class of flavonoids (flavones, flavonols, flavan-3-ols, isoflavones, flavanones, and anthocyanidins) and/ or their chemical structure, specifically in regards to the position and number of methoxy and phenolic group within their structure [38][39][40].…”
Section: Total Phenol and Flavonoid Contentmentioning
confidence: 99%